PENGELOLAAN KOLEKSI DI MUSEUM MUSIK INDONESIA SEBAGAI UPAYA PELESTARIAN WARISAN BUDAYA - Nita Siti Mudawamah (Fihris: Jurnal Ilmu Perpustakaan dan Informasi, 2021)
The Museum Music Indonesia is the only museum that houses a collection of music by Indonesian musicians. Located in Malang City, this museum has approximately 35.000 music collections of various types including cassettes, vinyl, compact disks, posters, magazines, musical instruments, audio equipment, and even artist/musician clothes. This paper aims to describe how the collection management at the Museum Music Indonesia uses a qualitative descriptive approach. The results found in the field include; Most of the collections contained in this music museum are obtained from grants from the music lovers community, collection management begins with the collection, data collection, presentation, and information to the public, the management is still done manually due to limited resources. With the cooperation and attention of all stakeholders, MMI can continue to live and develop as a preserver of the nation's treasures that are attractive to the community.